Sugar cane (Saccharum spp.) crop residue baling for energy purposes in Brazil - Ripoli, M. L C [UNESP]; Ripoli, T. C C; Gamero, Carlos Antonio [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2005)
The sugar cane crop according to several authors can generate, besides the industrialized stalks, an amount of crop residues from the order of 15 to 30% in weight of the aerial part of the plants, depending on the field conditions. The sugar cane area in Brazil is around 5.5×106 hectares, with an amount of 400.106 tons of stalks, with stalks yield of 72 tons.ha-1 (Unica, 2005). This study took place in a sugar cane plot (Latitude 22°46'S, Longitude 47°23'W and 600m of altitude) with 3% of slope, located in São Paulo State. The sugar cane variety was SP 80-1816, in its forth cut, 11 months old and with a planted row spacing of 1.40m. By other side, several sugar mills are bringing the crop residue to their patio to produce energy with the bagasse. One way for that is the baling operation to bring the crop residue at the sugar mill. Some fundamental variables were obtained to define the best set of machines to work with in sugar cane crop residue removal in the baling system among the studied ones, some of the variables were: Soil Index (T1 = 0.83%, T2 = 0.46%, T3 = 0.65%, T4 = 0.57%); Energy Efficiency (T1 = 82.48%, T2 = 83.88%, T3 = 82.83% and T4 = 82.97%) of the system and Effective Cost for Equivalent Energy in US$.EBP-1 (T1 = 11.10, T2= 10.46, T3 = 11.47 and T4 = 10.57) of the baled trash delivered at the sugar mill.
Keywords: Baling; Costs; Evaluation; Harvest crop residues; Sugar cane; Aerial parts; Crop residue; Energy purpose; Equivalent energy; Field conditions; Row spacing; Saccharum spp; Soil indices; Sugar mills; Agricultural wastes; Crops; Energy efficiency; Harvesting; Sugar (sucrose); Sugar factories; Sugars